Site-specific glycoproteomic characterization of ES-62: The major secreted product of the parasitic worm Acanthocheilonema viteae. (16th May 2019) - North, Simon J; Botchway, Kwamina; Doonan, James; Lumb, Felicity E; Dell, Anne; Harnett, William; Haslam, Stuart M
Abstract: ES-62 is the major secreted product of the parasitic filarial nematode Acanthocheilonema viteae and has potent anti-inflammatory activities as a consequence of posttranslational decoration by phosphorylcholine (PC). Previously, we showed that ES-62's PC was attached to N-linked glycans, and using fast atom bombardment mass spectrometry, we characterized the structure of the glycans. However, it was unknown at this time which of ES-62's four potential N-glycosylation sites carries the PC-modified glycans. In the present study, we now employ more advanced analytical tools—nano-flow liquid chromatography with high-definition electrospray mass spectrometry—to show that PC-modified glycans are found at all four potential N-glycosylation sites. Also, our earlier studies showed that up to two PC groups were detected per glycan, and we are now able to characterize N-glycans with up to five PC groups. The number per glycan varies in three of the four glycosylation sites, and in addition, for the first time, we have detected PC on the N-glycan chitobiose core in addition to terminal GlcNAc. Nevertheless, the majority of PC is detected on terminal GlcNAc, enabling it to interact with the cells and molecules of the immune system. Such expression may explain the potent immunomodulatory effects of a molecule that is considered to have significant therapeutic potential in the treatment of certain human allergic and autoimmune conditions.